Chinese herbal medicine hot package therapy and nursing management for a patient with cold-dampness stasis type abdominal cold pain caused by chronic pelvic inflammatory disease (中药热奄包治疗1例寒湿瘀滞型慢性盆腔炎腹部冷痛的护理体会) - SHEN Yueyue (申月月); ZHANG Rao (张绕); ZHU Lei (朱磊); XU Qian (许倩); LIU Xiaoyu (刘晓宇); LU Yin (卢英) (中西医结合护理)
This paper reviewed the Chinese herbal medicine hot package therapy and nursing management for a patient with cold-dampness stasis type abdominal pain caused by chronic pelvic inflammatory disease. Based on the Traditional Chinese Medicine syndrome differentiation and identification of syndrome type, the Chinese herbal medicine hot package therapy combined with comprehensive interventions such as dietary care, life support, and psychological care were carried out to relieve the cold-pain symptoms and improve the recovery of the patient. (本文总结1例采用中药热奄包治疗寒湿瘀滞型慢性盆腔炎腹部冷痛的护理经验, 基于中医辨证, 确定患者证型, 通过开展中药热奄包治疗, 并配合饮食护理、生活护理、心理护理等综合护理干预, 有助于减轻患者腹部冷痛, 加快患者恢复。)